Making a placement test based on vocabulary knowledge / Andrew Gorringe and John Anderson - Andrew, Gorringe; John, Anderson (Universiti Teknologi MARA, Kedah, 2014)
The object of this paper is to describe how the authors used vocabulary to create a valid and reliable placement test. First, the writers will explain the reasons for using vocabulary for placement testing purposes by looking at the literature on knowledge of vocabulary and its relationship to language ability. Next the paper will explain how the test was constructed and delivered to the test takers using the Moodle quiz module. It will then show how the test and test items were analysed using both classical test theory and item response theory. It will also show the reliability of the test and how the test was validated. Finally the paper will show how accurately the test placed the test takers. The results of this study demonstrate that using vocabulary knowledge as the basis for a placement test is an easy and efficient way for teachers to determine their students’ relative language ability. The study also shows that the test itself is both valid and reliable and that it accurately places students according to their language ability.